Serotonin modulates a depression-like state in Drosophila responsive to lithium treatment - Ariane-Saskia Ries (Nature Portfolio, 2017)
Features of major depressive disorder including lack of motivation, sleep disruption and cognitive deficit have been modelled in rodents. Here, the authors develop a new method to elicit a depression-like state inDrosophila, and uncover separable roles for different serotonin receptors in depression-like behaviour.